Pre-Columbian Transoceanic Contacts: Far-Out Fantasy, Unproven Possibility, or Undeniable Reality? - Jett, Stephen C. (Journal of Scientific Exploration, 2014)
The standard view has been that once the Americas were settled via Beringia, the human denizens of the Western Hemisphere were essentially cut off from interaction with peoples of the Old World. Here, I present multidisciplinary evidence that the hemispheres were, instead, interconnected by repeated voyages over millennia, resulting in profound influences on both sides of the oceans. I first examine arbitrary cultural traits (cosmology, calendrics, and art) and complex technologies (barkcloth/papermaking, the blowgun, metallurgy, weaving and dyeing, ceramics), then comment on likely relationships between certain Old and New World languages. A large number of cultivated plants and one or two species of domestic fowl, which could not have crossed oceans without human carriage, were shared between the hemispheres before—in most cases, long before—1492. Several tropical Old World human intestinal parasites that could not have entered the Americas via Beringia were also shared, some remarkably early. The geographical distributions of certain distinct human genetic markers imply important inputs to Mesoamerican and Andean populations from more than one overseas source. Studies of climatology, oceanography, and traditional watercraft and navigation show that early vessels were capable of ocean crossings via certain routes. These converging, essentially independent lines of evidence imply that we can no longer assume that the cultures of the two hemispheres evolved in parallel fashion in isolation from one another and according to “laws” discoverable through comparative studies. Keywords: culture—cultural diffusion—culture change—comparative studies—technology—cultivated plants—intestinal parasites—human genetics—ocean crossings—traditional watercraft—traditional navigation Of course, America had often been discovered before Columbus, but it had always been hushed up. — Oscar Wilde